Pelaksanaan Restorative Justice dan Pemenuhan Kepentingan Terbaik Korban di Kejaksaan Negeri Kota Metro - Kevin Subasa; Aziza Aziz Rahmaningsih; Al Rasid Hasbi Mubarak (Universitas Muhammadiyah Ponorogo, 2026)
The integration of Restorative Justice into the Indonesian criminal justice system marks a paradigm shift from a retributive framework to one that prioritizes restoration, reconciliation, and substantive justice. However, uncertainty remains regarding the use of Restorative Justice in embezzlement cases and the extent to which this framework can adequately serve the best interests of victims. This study aims to examine the application of Restorative Justice in handling embezzlement cases at the Metro City District Attorney's Office and evaluate the extent to which this approach serves the best interests of victims. The study methodology used is normative legal research complemented by an empirical approach, involving an examination of legislation, legal doctrine, and case studies of prosecution terminations based on Restorative Justice. The results indicate that the application of Restorative Justice at the Metro City District Attorney's Office has been implemented in accordance with Attorney General Regulation Number 15 of 2020, taking into account the requirements of the perpetrator as a first-time offender, a criminal sentence of less than five years, the existence of reconciliation, and the restitution of the victim's losses. This implementation has proven effective in fulfilling the best interests of victims through compensation, admission of guilt, and a swift and definitive resolution of the case. However, challenges remain, including inconsistent practices, the potential for subjectivity in prosecutors' discretion, and a persistent retributive paradigm within society. Therefore, strengthening regulations, technical guidelines, and increasing the capacity of officials are necessary to ensure a more consistent and accountable implementation of restorative justice